Endogenous cathelicidin production limits inflammation and protective immunity to Mycobacterium avium in mice. Issue 1 (31st October 2013) - Santos, José Carlos; Silva‐Gomes, Sandro; Silva, João Pedro; Gama, Miguel; Rosa, Gustavo; Gallo, Richard L.; Appelberg, Rui
Abstract The production of antimicrobial peptides, such as the cathelicidins, plays a prominent role in the innate immune response against microbial pathogens. Cathelicidins are widely distributed amongst living organisms, and the antimicrobial peptides generated by proteolysis of the precursor forms are typically cationic and α‐helical, a structure that facilitates their interaction and insertion into anionic bacterial cell walls and membranes, causing damage and promoting microbial death. Here, we found that mouse cathelicidin (Camp) expression was induced in bone marrow‐derived macrophages by infection with Mycobacterium avium in a TLR2‐ and TNF‐dependent manner. However, the endogenous production of the cathelin‐related antimicrobial peptide (CRAMP) was not required for the bacteriostasis of M. avium either in primary cultures of macrophages or in vivo, as shown by the use of CRAMP‐null mice. In contrast, the lack of Camp led to a transient improvement of M. avium growth control in the spleens of infected mice while at the same time causing an exacerbation of the inflammatory response to infection. Our data highlight the anti‐inflammatory effects of CRAMP and suggests that virulent mycobacteria may possess strategies to escape its antimicrobial activity.